Evaluation of the biological treatment of a real contaminated groundwater through reductive dechlorination biostimulation - Yaqoubi, Hafsa; Sassetto, Geremia; Presutti, Maria; Belfaquir, Mustapha; Matturro, Bruna; Rossetti, Simona; Lorini, Laura; Petrangeli Papini, Marco; Zeppilli, Marco (Frontiers in Chemical Engineering, 2025)
Chlorinated aliphatic hydrocarbons (CAHs) are common groundwater contaminants due to improper utilization in past industrial activity. Anaerobic reductive dechlorination, where bacteria use CAHs as electron acceptors, is crucial for bioremediation. Environmental conditions, such as nutrient availability and electron donors (i.e., molecular hydrogen), can influence the effectiveness of bioremediation processes. Also, bioremediation strategies like bioaugmentation (i.e., the supply of the enriched dechlorinating consortium) and bio-stimulation (i.e., the supply of electron donor) can improve CAHs removal performances. Here, a microcosm study is presented to assess the effectiveness of bioaugmentation with an enriched dechlorinating consortium for groundwater remediation. Target contaminants used were tetrachloroethane (TeCA), trichloroethylene (TCE) and sulphate ion. Various conditions, including biostimulation and bioaugmentation approaches were tested to evaluate the feasibility of biological treatment. Operating conditions, i.e., mineral medium and lactate, facilitated the dechlorination of TCE into ETH, leading to an increase in the dechlorinating population (Dehalococcoides mccartyi) to 67% of the total bacteria, with reductive dechlorination (RD) rates up to 7 µeq/Ld. Conversely, the RD performance of microcosms with real contaminated groundwater was negatively affected by the combined presence of TeCA and sulphate, indicated by a low abundance of D. mccartyi (<3%) and low RD rates (up to 0.39 µeq/Ld), suggesting that the native microbial population lacked the capacity for effective dechlorination. Moreover, the principal component analysis plot highlighted distinct groupings based on microbial community across different microcosm conditions, indeed, microbial community structures dominated by D. McCarty were associated with higher reductive dechlorination rates while non-augmented and non-stimulated microcosms reflected distinct microbial communities dominated by non-dechlorinating taxa. Additionally, RD decreased (48, 23, 22, and 14 µeq/Ld) with increasing sulphate concentrations (0, 150, 225, and 450 mgSO4 -2/L), further demonstrating the inhibitory effect of sulphate in the treated contaminated groundwater. Overall, this study highlights the complex interplay between environmental conditions, treatment strategies, and microbial communities in driving dechlorination processes. Specifically, the effectiveness of reductive dechlorination is heavily influenced by the availability of electron donors and the composition of the medium or groundwater, which can drive significant shifts in microbial community dynamics, either supporting or hindering the reductive dechlorination process.